Control of gray mold rot disease of tomato caused by Botrytis cinerea with emulsion formulated from Moringa oleifer Lam. crude extract - Ahmadu, Tijjani (2017)
Series of laboratory experiments were conducted with emphasis on the preparation of nano-emulsion formulations from active compounds in Moringa oleifera crude extracts and in vitro and in vivo evaluation of their bio-efficacy against Botrytis cinerea causing gray mold rot disease on tomato. In total, nine isolates were successfully isolated from infected tomato sampled from Cameron Highlands, Pahang, Malaysia in 2015. The isolates were identified based on morpho-cultural characteristics such as mycelial texture, conidia shapes and sizes, and sclerotia forms. Conidia (n=40) measured 9.7-17.1 × 6.6-10.5 μm, were smooth one-celled, ellipsoidal, globose or ovate and borne in clusters on branching tree-like conidiophores. To confirm the morphological identification, the primer pair ITS4/ITS5 (ITS region) of rDNA and part of Glyceraldehyde-3-phosphate dehydrogenase gene (G3PDH) were used for amplification and sequencing of the isolates (BCH01 to BCH09). The sequences obtained (GenBank Accession No. KU992692-KU992700 for ITS and KY201456- KY201464 for G3PDH) showed 99-100% homology with B. cinerea isolates in the GenBank nucleotides database. Based on the pathogenicity assay, the isolates showed variations in their levels of severity. In ripen tomato fruits, the per cent disease severity ranged from 36 to 97%, with maximum per cent observed in BCH07 (97%) and minimum in BCH04 (36%). Among the organic solvents used in the extraction of the bioactive compounds, methanol gave the highest (14.16%) percentage extraction yield compared to ethanol (10.23%), ethyl acetate (5.24%), hexane (2.3%) and distilled water (1.71%). SEM and TEM micrographs on the effect of the crude extracts of M. oleifera on the conidia and mycelium of B. cinerea treated with MIC concentration revealed irreversible surface and ultra-structural changes that include lysis, shrinkage, pore formation, aggregation and vacuolation compared to the controls. The results of GC-MS led to the identification of 67 volatile chemical compounds with n-Hexadecanoic acid, Malonic acid, 6-decanoic acid, (Z)-, .beta.-l-Rhamnofuranoside,5-O-acetyl-thio-octyl-, 2-Dimethyl (trimethylsilylmethyl) silyloxymethyl tetrahydrofuran, and 4H-Pyran-4-one, 2,3-dihydro-3,5-dihydroxy-6-methyl- as the predominant in the extract. Further chemical elucidation of the crude extracts performed with LC-MS/MS showed the presence of phenylvaleric acid, caffeic acid derivative, quinic acid, apigenin-6,8-di-C-β-D-glucopyranoside (Vicenin II) , Apigenin 6 C glucoside, quercetin-3-O-glucoside dimer and kaempferol 3-o glucoside dimer as the major non-volatile chemical compounds, which are mostly flavones, flavonois and phenolic acids. The results on the characterization of the formulations showed that all formulations were stable at 25°C for two months and 54°C for one month. All formulations have particle size of less than 100 nm, PDI from 0.108-0.415, surface tension below 30 mN/m, viscosity less than 60 mPas, zeta potentials less than 40 mV and pH less than 6.00. TEM micrographs of the formulations confirmed the spherical shape of nano-emulsions and the particle size of less than 100 nm as measured with Malvern Zsizer instrument. The results of SEM and TEM micrographs on the effect of the formulations on the conidia and mycelium of B. cinerea confirmed the irreversible surface and ultra-structural alterations such aggregation, abnormal growth, lysis, reduced hyphal diameter and length, destruction of the organelles and irregular cell wall shape compared to the controls. In vivo evaluation was conducted with healthy tomato fruits via preventive and curative treatments. The results on in vivo indicated 93.3% to 100% disease reduction in treated fruits under preventive method compared with 0% in the negative controls. Results on the effects of the formulations on the post-harvest quality of the fruits showed that % weight loss was as low as 0.72%, loss in firmness (3.09%) and CIE values (L*=37.72, a*=29.15, b*=19.98) for colour, on tomatoes treated with F13 the formulations under preventive method. Similarly, chemical analysis of the F13 formulations treated fruits showed that the final percent TSS was 4.18%, AA (20.95 mg/ml), TA (0.34%) and pH (4.05). Mineral content analysis revealed that tomatoes treated with F13 formulations gave the best results on mineral contents with K (201.96 mg/ml), Ca (28.29 mg/ml), Mg (20.56 mg/ml) and Zn (0.42 mg/ml).